2019
DOI: 10.1002/jbio.201960087
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of cerebral blood perfusion and cerebral edema using swept‐source optical coherence tomography

Abstract: The progression of ischemic cerebral edema (CE) is closely related to the level of cerebral blood perfusion (CBP) and affects each other.Simultaneous detection of CBP and CE is helpful in understanding the mechanisms of ischemic CE development. In this article, a wide field of view swept-source optical coherence tomography system was used to detect CE status and CBP levels simultaneously in middle cerebral artery occlusion rats. Images reflecting these two physiological states can be reconstructed with only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Moreover, the edema brain will significantly reduce the metabolism and blood perfusion. Thus, the values are set to 10000 W/m 3 for metabolic heat source [43], and 0.006644 1/s for blood perfusion rate in edema region [44].…”
Section: E the Effect Of Edema On Eofmentioning
confidence: 99%
“…Moreover, the edema brain will significantly reduce the metabolism and blood perfusion. Thus, the values are set to 10000 W/m 3 for metabolic heat source [43], and 0.006644 1/s for blood perfusion rate in edema region [44].…”
Section: E the Effect Of Edema On Eofmentioning
confidence: 99%
“…Optical coherence tomography (OCT), which reconstructs depth information images of biological tissues using backscattered light from the sample, has the advantages of non-contact, non-invasive and a high resolution [21]. OCT technology appeared in the 1990s and gradually transited to frequency domain OCT from time domain OCT [22]. Over the past two decades, various OCT-based technologies have arisen.…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple clinical studies have shown that hyperosmotic therapy dehydrates mainly the non-lesioned tissue, and its capacity in eliminating excess water content in the edema region is rather limited [ 16 , 21 , 30 , 43 ]. For the region involving CE, the edematous brain tissue squeezes the surrounding blood vessels, which reduces the cerebral blood perfusion resulting in the low efficiency of hyperosmotic therapy [ 34 ]. Moreover, the damaged blood circulation in the edema region causes vascular leakage [ 2 ], which also weakens the dehydration effect in the edema region.…”
Section: Introductionmentioning
confidence: 99%